Gender differences in self-reported health and psychological distress among New Zealand adults - Santosh Jatrana (Demographic Research, 2021)
Background: Previous research that examines gender differences in health does not rigorously assess the gender-related differential 'exposure' and differential 'vulnerability' hypotheses; i.e., does not try to identify the 'direct' (unmediated) effect of gender or quantify the relative importance of different risk factors for each gender. Objective: I test the hypothesis that gender differences in health (self-assessed health (SAH) and psychological distress (PD)) are due to indirect or mediating effects via socioeconomic and behavioural factors, and are not a direct effect of gender on health. Methods: Data (N = 18,030) from the third wave of the Survey of Family, Income and Employment (SoFIE) and multivariate logistic regression analyses are used to test gender differences in SAH and psychological distress. Results: The analyses show that women are less likely to report poor self-assessed health but more likely to report moderate-to-high psychological distress. Differential exposure of men and women to the determinants of health did not completely account for gender differences in health. Gender-specific differences in vulnerability were found only in the direct effects of age, and employment status. Conclusions: These results suggest that much, but not all, of the association between gender and health is mediated by socioeconomic factors. Contribution: This paper extends the literature on gender differences in health through a detailed empirical examination of the differential exposure of men and women to sociodemographic, socioeconomic, and health behaviour factors (i.e., indirect effects), and the differential vulnerability of women and men to this exposure (i.e., direct effects).